2010
DOI: 10.1523/jneurosci.3357-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Dynamics of Fast Ripples in the Epileptic Hippocampus

Abstract: Fast ripples are a type of transient high-frequency oscillations recorded from the epileptogenic regions of the hippocampus and the temporal cortex of epileptic humans and rodents. These events presumably reflect hypersynchronous bursting of pyramidal cells. However, the oscillatory spectral content of fast ripples varies from 250 to 800 Hz, well above the maximal firing frequency of most hippocampal pyramidal neurons. How such high-frequency oscillations are generated is therefore unclear. Here, we combine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
207
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(222 citation statements)
references
References 72 publications
13
207
2
Order By: Relevance
“…Juxtacellular recordings revealed bursts of action potentials aligned with individual fast ripple cycles (Ibarz et al, 2010) and with large population spikes (Bragin et al, 2011). However, a poor correlation between the firing frequency of individual cells and the dominant spectral peak in the local EEG confirms that fast ripples emerge as a network phenomenon and that single cells rarely fire faster than 400 Hz.…”
Section: Fast Ripples and The Epileptic Hippocampus: The Out-of-phasementioning
confidence: 96%
See 4 more Smart Citations
“…Juxtacellular recordings revealed bursts of action potentials aligned with individual fast ripple cycles (Ibarz et al, 2010) and with large population spikes (Bragin et al, 2011). However, a poor correlation between the firing frequency of individual cells and the dominant spectral peak in the local EEG confirms that fast ripples emerge as a network phenomenon and that single cells rarely fire faster than 400 Hz.…”
Section: Fast Ripples and The Epileptic Hippocampus: The Out-of-phasementioning
confidence: 96%
“…Analysis of voltage depth profiles of pathological HFOs in the kainic acid model showed that the maximum of their amplitude and the location of their sinkssources (Ibarz et al, 2010) were in the cellular layers of the dentate gyrus or of CA1 area of hippocampus. Discharges of identified granular (Bragin et al, 2011) and pyramidal cells are phase locked with troughs of locally recorded pathological HFOs.…”
Section: Evidence For Hfos In Experimental and Clinical Epilepsymentioning
confidence: 99%
See 3 more Smart Citations